Properties of oxaloacetate decarboxylase from Veillonella parvula. - Ng, S K (1982)
Oxaloacetate decarboxylase was purified to 136-fold from the oral anaerobe Veillonella parvula. The purified enzyme was substantially free of contaminating enzymes or proteins. Maximum activity of the enzyme was exhibited at pH 7.0 for both carboxylation and decarboxylation. At this pH, the Km values for oxaloacetate and Mg2+ were at 0.06 and 0.17 mM, respectively, whereas the Km values for pyruvate, CO2, and Mg2+ were 3.3, 1.74, and 1.85 mM, respectively. Hyperbolic kinetics were observed with all of the aforementioned compounds. The Keq' was 2.13 X 10(-3) mM-1 favoring the decarboxylation of oxaloacetate. In the carboxylation step, avidin, acetyl coenzyme A, biotin, and coenzyme A were not required. ADP and NADH had no effect on either the carboxylation or decarboxylation step, but ATP inhibited the carboxylation step competitively and the decarboxylation step noncompetitively. These types of inhibition fitted well with the overall lactate metabolism of the non-carbohydrate-fermenting anaerobe.